Demand Side Management inside a Smart House - Šipoš, Mario; Primorac, Mario; Klaić, Zvonimir (International Journal of Electrical and Computer Engineering Systems, 2015)
The upgraded traditional grid, also known as the smart grid, that incorporates information and communications technologies will change not only electricity production but also consumption. In combination with Photovoltaics (PV) and electrical storage, demand side management (DSM) is a promising solution for net-zero energy building (NZEB). NZEB will be able to produce energy for its own needs and also feed a surplus back to the grid. In scientific papers, it has already been proven that the use of electrical energy storage can improve the power quality and store variable production of renewable energy. Smart meters are a step forward because they enable a two-way communication between a customer and a utility. In this way, it will be possible to monitor consumption and electricity prices on the market in real time. Furthermore, this will enable the consumer to turn off devices that are large loads, or let the DSM system known as load management do its job such to reduce energy consumption in a given period. DSM will automatically switch off a big load in a manner that does not disturb user comfort. Smart appliances at the end-user level such as the Internet protocol (IP) addressable appliance controlled by external signals from the utility or end-user will enable load shifting to off-peak periods. Solar radiation is prevalent everywhere and can be used to generate electricity at the point of consumption, thereby reducing the losses in transmission. Only one hour of solar radiation is sufficient to cover the annual consumption; this shows that the future of low-carbon energy production lies in the use of solar radiation.